Austrochthonius transversus Beier 1964 - Novák, János; Dányi, László (Zenodo, 2018)
transversus Beier, 1964 Austrochthonius chilensis transversus Beier 1964: 488, fig. 1. Syntypes. HNHM Pseudoscorp-44: 5 ex. [3 ♂, 1 ♀, 4 nymphs according to original description] “ Austrochthonius transversus n. sp., det. Beier, ♂ ♀, Typen!”, “No. 42.” [Argentina, Rio Negro, El Bolsón, Mt. Piltriquitron, 1150 m, from leaf litter in a forest of Maytenus boaria with Berberis darwini and Nothofagus antarctica close to a spring, 16.XI.1961, leg. Gy. Topál]. HNHM Pseudoscorp-45: 4 ex. [2 ♂, 8 ♀, 5 nymphs according to original description] “ Austrochthonius transversus n. sp., det. Beier, ♂ ♀, Paratypen ”, “No. 24.” [Argentina, Rio Negro, El Bolsón, Mt. Piltriquitron, 1500 m, leaf litter in a Nothofagus pumilio forest, 23.X.1961, leg. Gy. Topál]. HNHM Pseudoscorp- 46: 3 ex. [3 ♂, 7 ♀, 1 nymph according to original description] “ Austrochthonius transversus n. sp., det. Beier, ♂ ♀, Paratypen ”, “No. 19.” [Argentina, Mt. Piltriquitron, 1100 m, leaf litter in a bog forest of Nothofagus antarctica , 1. VII.1961, leg. Gy. Topál]. HNHM Pseud. -912: 3 ♀ “ Austrochthonius transversus n. sp. det. Beier, ♀ Paratypen ”, “No. 49.” [Argentina, Rio Negro, El Bolsón, Mt. Piltriquitron, 1150 m, leaf litter in a Maytenus and Berberis darwini forest, moderately wet, 22.VIII.1961, leg. Gy. Topál]. HNHM Pseud. -913: 1 nymph. “ Austrochthonius transversus n. sp. det. Beier, Nymph. ”, “Arg. [Argentina] El Bolson [sic], No. 98., 22.IX.1961; [leg.] Gy. Topál ” [Valley of Rio Azul, 320 m, from moss from rocks]. HNHM Pseud. -914: 3 ex. [4 ♂, 2 nymphs according to original description] “ Austrochthonius transversus n. sp. det. Beier, ♂ Paratypen ”, “No. 21.” [Argentina, El Bolsón, Mt. Piltriquitron, 920 m, leaf litter in a Mulinum- Lomatia stock, 4.X.1961, leg. Gy. Topál]. HNHM Pseud. - 915: 2 ♀ “ Austrochthonius transversus n. sp. det. Beier, ♀ Paratypen ”, “No. 43” [Argentina, El Bolsón, Mt. Piltriquitron, 1150 m, Fallaub im Wald aus Nothofagus pumilio , 6.X.1961, leg. Gy. Topál]. Current status. Valid, as Austrochthonius chilensis ...